GOVERNMENT RESPONSIBILITY FOR THE FREE NUTRITIONAL MEAL PROGRAM POLICY BASED ON THE PRINCIPLE OF LIABILITY IN CASES OF STUDENT POISONING - Zahra Ekasiwi Megawati (Universitas Negeri Semarang, 2026)
The Free Nutritious Meal Program (MBG) is an affirmative action policy implemented by the government within the framework of a welfare state. Its purpose is to fulfill children's constitutional rights to nutrition, health, and protection, as guaranteed in the 1945 Constitution of the Republic of Indonesia. This program aims to improve the quality of the workforce by providing nutritious food to students, toddlers, pregnant women, and breastfeeding mothers. However, in 2025, during its implementation, several cases of mass poisoning occurred in several areas, causing thousands of students to experience health problems. These incidents have raised legal issues related to the application of the principle of responsibility, in determining the form and scope of government responsibility as a direct provider of public services. This research uses a normative legal approach with statutory, conceptual, and case studies methods. The legal materials analyzed include Law Number 30 of 2014 concerning Government Administration, Law Number 18 of 2012 concerning Food, Law Number 8 of 1999 concerning Consumer Protection, the Civil Code, and regulations governing food safety and the management of food safety products. This analysis examines the application of fault-based and absolute liability in situations where government action is taken. This research shows that the government cannot avoid responsibility simply by involving third parties, as MBG is a form of public authority. However, obstacles remain, including inconsistent regulations and a lack of clear compensation for affected individuals. Therefore, legal regulations need to be harmonized and improved to ensure legal certainty and adequate protection for children, the most vulnerable group